(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The objective of this work was to discuss about broad themes of environmental education involving teaching-research-extension in three different Public Institutions in the city of São Gabriel, Rio Grande do Sul. The work with the three Public Institutions (Municipal Schools, Military Organization and Federal University of Pampa) took place during two years (2017-2018), environmental education topics were discussed through lectures and production of seedlings of native and exotic vegetable species with recovery of degraded areas and/or establishment of orchards / afforestation. The lectures were given to about 60 students from schools and 70 members from the Military Organization with satisfactory achievement, being reflected in the practical activities, with sowing and planting of fifteen different species (around 3500 seedlings) in areas established by the Public Institutions. It can be said that the university extension represented a privileged and enriching environment for those involved in the activities presented. In the same way, the project stimulated environmental awareness among the members involved (academic and municipal community), as well as being an excellent way of disclosure of the Federal University of Pampa.